Exploring acetylene chemistry in superbasic media: A theoretical study of the effect of water on vinylation and ethynylation reactions with acetylene in KOH/DMSO and NaOH/DMSO systems. (6th December 2016) - Vitkovskaya, Nadezhda M.; Orel, Vladimir B.; Kobychev, Vladimir B.; Bobkov, Alexander S.; Larionova, Elena Yu.; Trofimov, Boris A.
Abstract: A rapidly developing approach adding new dimensions to acetylene chemistry relying on employment of high basicity media such as alkali metal hydroxide suspensions in dimethyl sulfoxide (DMSO) has been, for the first time, investigated theoretically using ab initio models. Extending our recently introduced model of superbase catalysis with a nondissociated KOH (or NaOH) participation, we present here a model for a superbasic reaction center with the first solvation shell explicitly included. The alkali metal hydroxides in a DMSO solution were found to form KOH·5DMSO and NaOH·4DMSO complexes that are stabilized due to the interligand interaction. Our present MP2/6‐311++G**//B3LYP/6‐31+G* computations show that 1 and 2 water molecules can build themselves into the MOH close surrounding without substantially perturbing the DMSO ligands and easily travel between different insertion positions. Our results predict that the activation energies in the series of reactions of nucleophilic addition to a triple bond with water, methanol, methanethiol, sodium hydrosulfide, and acetone in the presence of dihydrated complexes should be larger than those obtained with the participation of monohydrated ones, which is in fair agreement with the experimental findings. The present model also explains an increase in the ethynylation reaction yield in the presence of water by suppression of the competitive enolization reaction. Abstract : The alkali metal hydroxides in a DMSO solution were found to form KOH·5DMSO and NaOH·4DMSO complexes that are stabilized due to the interligand interaction. One and two water molecules can build themselves into the MOH close surrounding without substantially perturbing the DMSO ligands and easily travel between different insertion positions. The activation energies of water, methanol, methanethiol, sodium hydrosulfide, and acetone nucleophilic addition to a triple bond in the presence of dihydrated complexes should be larger than those obtained with the participation of monohydrated ones, which is in a fair agreement with the experimental findings.